Experimental studies of Elaphostrongylus rangiferi in reindeer (Rangifer tarandus tarandus): Clinical observations - Handeland, K.; Skorping, A.; Stuen, S.; Slettbakk, T. (Rangifer, 1994)
Clinical observations were made on 12 reindeer calves (Rangifer tarandus tarandus) experimentally infected with 200-1000 infective larvae of Elaphostrongylus rangiferi and autopsied 2.5-196 days post inoculation (p.i). Seven experimental animals autopsied later than 20 days p.i. all developed neurologic signs starting 4-8 weeks p.i. In six of these animals, signs lasted until autopsy 0-12 weeks after onset. The seventh animal recovered completely after a disease period lasting five months. A dose-response relationship between the infective dose and severity of signs was observed. Clinical signs observed in all affected animals were paraparesis, tail paresis and posterior ataxia. Other signs included lowered head, general weakness, lameness, tetraparesis, scoliosis, anal hypotonia, head and neck turn, depression and reduced vision. The prepa-tent period was 4-4.5 months.